1991
DOI: 10.1002/jso.2930470304
|View full text |Cite
|
Sign up to set email alerts
|

The role of intraluminal radiotherapy and concurrent 5‐fluorouracil infusion in the management of carcinoma esophagus: A pilot study

Abstract: Fifty patients with carcinoma of the esophagus were entered in a randomized pilot study to test the efficacy of intraluminal radiotherapy (ILRT) and concurrent 5-fluorouracil (5-FU) infusion. The median age was 65 years, with 80% having middle third lesions; in 62%, the lesions were longer than 5 cm. After external beam therapy of 50 Gy in 5 weeks, patients were randomized to receive chemotherapy. Significant improvement in dysphagia was recorded in 76% patients with complete response in 47 cases ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…As published earlier, 15 the addition of 5-¯uorouracil with intraluminal brachytherapy suggested improved results. It was decided to continue the 5-¯uorouracil for both groups using 500 mg/m 2 i.v.…”
Section: Concurrent Chemotherapy With Intraluminal Brachytherapysupporting
confidence: 59%
See 1 more Smart Citation
“…As published earlier, 15 the addition of 5-¯uorouracil with intraluminal brachytherapy suggested improved results. It was decided to continue the 5-¯uorouracil for both groups using 500 mg/m 2 i.v.…”
Section: Concurrent Chemotherapy With Intraluminal Brachytherapysupporting
confidence: 59%
“…At our centre, intraluminal brachytherapy for carcinoma of the esophagus has been used since 1988. The results of a randomized study using ILRT alone vs. ILRT + 5-¯uorouracil following external beam radiation for radical treatment, 15,16 as well as in palliation for advanced/recurrent disease, 17 have been encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have reported improved swallowing ranging from 56% to 96% for a variable period of time using the combination of intraluminal radiation at either a low or high dose rate and external beam radiation therapy 10 , 15 , 34 , 38 , 44 , 47 , 48 . In the present series, 43% of patients showed an improvement in swallowing and another 47% were able to maintain pretreatment swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…As published earlier, 15 the addition of 5‐fluorouracil with intraluminal brachytherapy suggested improved results. It was decided to continue the 5‐fluorouracil for both groups using 500 mg/m 2 i.v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation